Models and methods for assessing spatial parameters of investment projects and urban reconstruction programs - Вielienkova O.; Koval , O; Bozhynskyi , M; Scherbak , I; Ben , O (Ways to Improve Construction Efficiency, 2024)
Modern processes of reconstruction of Ukrainian cities are taking place in conditions of significant socio-economic transformations caused by the consequences of war destruction, moral and physical deterioration of urban infrastructure, as well as the need to ensure balanced spatial development. In this regard, it is urgent to improve models and methods for assessing spatial parameters of investment projects and urban reconstruction programs that cover various types of objects - residential, public, industrial, religious buildings and structures. Existing methodological approaches are mostly focused on financial and economic assessment, while spatial, environmental, social and energy-efficient aspects remain fragmentarily taken into account or presented as auxiliary criteria. The need to improve such models lies in the transition from purely economic analysis to a comprehensive spatial and functional assessment based on the principles of sustainable development and digital transformation. A promising direction is the integration of information modeling (BIM, CIM) with geographic information technologies (GIS), which allows combining technical and economic indicators of investment projects with the parameters of the spatial organization of urban areas. Such digital models will contribute to a more accurate determination of the effectiveness of reconstruction measures, optimization of the use of territories, assessment of the impact of projects on social infrastructure and the environment. Further development of the evaluation methodology should include the use of multi-criteria decision-making methods (AHP, TOPSIS, SMART), methods of estimating the cost during the life cycle of buildings (LCC - Life Cycle Costing), as well as approaches to assessing energy efficiency, thermal modernization and cost management in the dynamics of the life cycle of the facility. It is also important to develop an integrated system of indicators that takes into account investment attractiveness, the level of social efficiency, spatial balance and compliance with strategic plans for the development of the city. Thus, improving models and methods for assessing spatial parameters of urban reconstruction investment projects creates the basis for improving the quality of management decisions, effective resource allocation, and the formation of a scientifically sound policy for the restoration and modernization of the urban environment based on the principles of sustainable development, digitalization, and energy efficiency.